Type 1 diabetes mellitus in the context of high levels of rural deprivation: differences in demographic and anthropometric characteristics between urban and rural cases in NW Ethiopia - Balcha, Shitaye A.; Phillips, David I.; Trimble, Elisabeth R. (Frontiers in Clinical Diabetes and Healthcare, 2024)
Background While there is increasing evidence for an altered clinical phenotype of Type 1 diabetes in several low-and middle-income countries, little is known about urban-rural differences and how the greater poverty of rural environments may alter the pattern of disease. Objective Investigation of urban-rural differences in demographic and anthropometric characteristics of type 1 diabetes in a resource-poor setting. Research design and methods Analysis of a unique case register, comprising all patients (rural and urban) presenting with Type 1 diabetes over a 20 yr. period in a poor, geographically defined area in northwest Ethiopia. The records included age, sex, place of residence, together with height and weight at the clinical onset. Results A total of 1682 new cases of Type 1 diabetes were registered with a mean age of onset of 31.2 (SD 13.4) yr. The patients were thin with 1/3 presenting with a body mass index (BMI) <17kg/m2. There was a striking male predominance of cases when clinical onset was between 20 and 35 yr., this was more marked in the very poor rural dwellers compared to the urban population. While most patients with Type 1 diabetes presented with low BMIs and reduced height, stunting preferentially affected rural men. Conclusions These data have led to the hypothesis that complex interactions among poor socioeconomic conditions in early life affect both pancreatic function and the development of autoimmunity and provide a possible explanation of the unusual phenotype of Type 1 diabetes in this very poor community.